2020
DOI: 10.1177/1038416220901808
|View full text |Cite
|
Sign up to set email alerts
|

Applying career human agency theory to practice

Abstract: This article elaborates the emerging career human agency theory and its applicability to career psychology practice. Using Bandura’s human agency theory as a foundation, career human agency theory is a meta-theory that integrates key tenets from major theories in vocational and career psychology. It presents an endeavour of theoretical integration to conceive and understand career issues and vocational behaviours. The article provides a brief overview of career human agency theory, indicating its postmodern co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…While we agree that the Korean context negatively influenced women's careers (Kim et al, 2019), our study also showed how highly educated women responded to negative chance events such as in childcare, the gendered workplace and the current jobs that did not match with their career goals. Negative chance events do not necessarily bring about negative career outcomes (Akkermans et al, 2018;Chen and Hong, 2020): our participants' negative work experiences motivated them to pursue a doctoral degree as an alternative, which led them to obtain a doctoral degree and to land in academic jobs as positive career outcomes, though not all secured tenure positions.…”
Section: Motivationsmentioning
confidence: 92%
See 1 more Smart Citation
“…While we agree that the Korean context negatively influenced women's careers (Kim et al, 2019), our study also showed how highly educated women responded to negative chance events such as in childcare, the gendered workplace and the current jobs that did not match with their career goals. Negative chance events do not necessarily bring about negative career outcomes (Akkermans et al, 2018;Chen and Hong, 2020): our participants' negative work experiences motivated them to pursue a doctoral degree as an alternative, which led them to obtain a doctoral degree and to land in academic jobs as positive career outcomes, though not all secured tenure positions.…”
Section: Motivationsmentioning
confidence: 92%
“…Some women choose career breaks voluntarily while others involuntarily decide career interruptions. Such different responses result from an interplay of human agency and social and cultural contexts as suggested in extant research on career chance events (Akkermans et al, 2018(Akkermans et al, , 2020Chen and Hong, 2020;Hirschi and Valero, 2017;Kim, 2020;Kim et al, 2019;Kindsiko and Baruch, 2019;Krumboltz, 2009;Rice, 2014) and on career interruptions (Bian and Wang, 2019;Elley-Brown et al, 2018;Grant-Vallone and Ensher, 2011;Harman and Sealy, 2017;Zimmerman and Clark, 2016). When women encounter unpredictable events in their careers, their decisionmaking about career interruptions is determined by their individual characteristics, social and cultural contexts.…”
Section: Responsesmentioning
confidence: 99%
“…Keele et al (2020) analyse career choice issues through student personal management, recognizing their uniqueness and core values, informing and educating about career opportunities and the active market, and safe career planning with the help of competent mentors and family participation. Chen & Hong (2020) point out such elements as career intentionality through comprehensive information, career forethought with rational goals, career self-reflectiveness, i.e. the ability to know and reflect on oneself and one's actions in a social, cultural, immediate environment.…”
Section: Previous Literature Reviews and Synthesesmentioning
confidence: 99%
“…Therefore, students need help in choosing a career so that in the future they could become self-confident citizens, able to integrate in the ever-changing labour market conditions (Surgėlienė, 2014). However, according to Surgėlienė (2014), Keele, Swann, & Davie-Smythe (2020), Chen & Hong (2020), Yang & Wong (2020), even though the system of career education at school has received great interest and is constantly updated it is still not consistent. There are multiple barriers for pupils to explore their future career possibilities and to take the right actions on that, especially for various vulnerable groups to whom this service is restricted due to certain internal and external conflicts.…”
Section: Introductionmentioning
confidence: 99%
“…Positive compromise (Chen, 2004) and life–career reengagement (Chen, 2011a) illustrate pertinent attempts toward this end. Along with the same line, much is to be gained via the presentation of the most recent endeavors in meta-theory development and theoretical integration as a viable alternative to describe and understand the human intention and action in their career contexts (Chen & Hong, 2020).…”
mentioning
confidence: 99%